Cyclic beta-(1,2)-glucan synthesis in Rhizobiaceae: roles of the 319-kilodalton protein intermediate. - Castro, O A (1996)
Cyclic beta-(1,2)-glucans are synthesized by members of the Rhizobiaceae family through protein-linked oligosaccharides as intermediates. The protein moiety is a large inner membrane molecule of about 319 kDa. In Agrobacterium tumefaciens and in Rhizobium meliloti the protein is termed ChvB and NdvB, respectively. Inner membranes of R. meliloti 102F34 and A. tumefaciens A348 were first incubated with UDP-[14C]Glc and then solubilized with Triton X-100 and analyzed by polyacrylamide gel electrophoresis under native conditions. A radioactive band corresponding to the 319-kDa protein was detected in both bacteria. Triton-solubilized inner membranes of A. tumefaciens were submitted to native electrophoresis and then assayed for oligosaccharide-protein intermediate formation in situ by incubating the gel with UDP-[14C]Glc. A [14C]glucose-labeled protein with an electrophoretic mobility identical to that corresponding to the 319-kDa [14C]glucan protein intermediate was detected. In addition, protein-linked radioactivity was partially chased when the gel was incubated with unlabeled UDP-Glc. A heterogeneous family of cyclic beta-(1,2)-glucans was formed upon incubation of the gel portion containing the 319-kDa protein intermediate with UDP-[14C]Glc. A protein with an electrophoretic behavior similar to the 319-kDa protein intermediate was "in gel" labeled by using Triton-solubilized inner membranes of an A. tumefaciens exoC mutant, which contains a protein intermediate without nascent glucan. These results indicate that initiation (protein glucosylation), elongation, and cyclization were catalyzed in situ. Therefore, the three enzymatic activities detected in situ reside in a unique protein component (i.e., cyclic beta-(1,2)-glucan synthase). It is suggested that the protein component is the 319-kDa protein intermediate, which might catalyze the overall cyclic beta-(1,2)-glucan synthesis.